PENGARUH PENDAPATAN TERHADAP PERMINTAAN PROPERTI KOMERSIAL DAN KEPUTUSAN INVESTASI DI KOTA SEMARANG - Abubakar, Valdin Lazuardi; Pantawis, Setyo Pantawis (ECONBANK: Journal of Economics and Banking, 2020)
This study aims to obtain empirical evidence of the effect of income on property demand and property investment decisions in Semarang City. Research gaps and practical data indicate that an increase in income does not always coincide with an increase in decisions to investment dicisions. The independent variable in the study is income, while the dependent variable are investment decisions and property demand. The population used in this study are residents of Semarang City who purchase commercial properties for future investment purposes and number of sampe is 97 people, taken by purposive sampling technique. The data collection method used a questionnaire. The findings of this study prove there is a positive-significant effect of the income on investment decisions and on property demand.